2021
DOI: 10.1186/s12893-021-01375-0
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic and pathological features of metaplastic squamous cell carcinoma of the breast: a case series

Abstract: Objective The aim of this study was to evaluate the sonographic features and to compare the sonographic findings with the pathologic features. Methods The sonographic and pathological features of all patients were retrospectively reviewed. Results All these 9 patients presented with a palpable breast mass first found by the patient before presentation. The median diameters were 3.67 cm. On two-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Upon sonographic examination, the most distinctive indications of MBC have been reported to be the presence of masses exhibiting a complex cystic and solid echo pattern, as well as posterior acoustic enhancement ( 31 - 35 ). Our research revealed that 50.0% of MBC lesions exhibited complex cystic and solid components, while 95.0% of MBCs were characterized by posterior acoustic enhancement, which aligns with prior research ( 33 ). The cystic areas might be caused by necrosis, hemorrhage, or cystic degeneration ( 13 ).…”
Section: Discussionsupporting
confidence: 91%
“…Upon sonographic examination, the most distinctive indications of MBC have been reported to be the presence of masses exhibiting a complex cystic and solid echo pattern, as well as posterior acoustic enhancement ( 31 - 35 ). Our research revealed that 50.0% of MBC lesions exhibited complex cystic and solid components, while 95.0% of MBCs were characterized by posterior acoustic enhancement, which aligns with prior research ( 33 ). The cystic areas might be caused by necrosis, hemorrhage, or cystic degeneration ( 13 ).…”
Section: Discussionsupporting
confidence: 91%
“…SCC of the breast is a histological subtype of metaplastic carcinoma with similar clinical features to non-specific ER-negative invasive breast cancer [ 1 ], despite reports of HER2 overexpression [ 10 , 11 ]. Most cases present as palpable masses and are identified as mass lesions on ultrasonography or mammography [ 12 ]. Additional symptoms besides breast lumps, such as skin ulcers and fungal infections can affect the chest wall [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We described different presentations of immunohistochemistry in different component, to expect helping therapy. 7 , 8 SATB2 is a marker of osteoblastic differentiation in bone tumors. 9 So the positive of SATB2 confirmed osseous differentiation of the tumor.…”
Section: Discussionmentioning
confidence: 99%